Historicity of Islamic Inheritance Law in Indonesia and Turkey - Mega Puspita; Ahmad Rezy Meidina (Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This article talks about renewal in the field of Islamic family law regarding inheritance. Islamic inheritance law is a law that regulates the inheritance of the assets of someone who has died and is given to those who are entitled. Islamic inheritance law in Indonesia is regulated in KHI Articles 176-191, this rule is also influenced by the school of thought that is developing in Indonesia, namely the Shafi'i. The basis for the renewal of Islamic Inheritance Law is the obligatory will, in which according to some Islamic thinkers, non-Muslim heirs can receive a share of the heir's assets through the obligatory will. Meanwhile, inheritance law in Turkish civil regulations has been regulated in the third book. The third book contains regulations on an inheritance without a will and these regulations are adopted from Swiss civil regulations. The Swiss civil code replaces Turkish law with the Hanafi school. Inheritance law in Turkey has the principle of equality between men and women so that they get the same distribution of inheritance.